Knowledge mapping of targeted immunotherapy for myasthenia gravis from 1998 to 2022: A bibliometric analysis - Su, Yue; Ruan, Zhe; Wang, Rui; Hao, Sijia; Tang, Yonglan; Huang, Xiaoxi; Gao, Ting; Li, Zhuyi; Chang, Ting (Frontiers in Immunology, 2022)
Background The treatment of myasthenia gravis (MG) has advanced from steroids and traditional immunosuppressants to targeted immunotherapy. Targeted immunotherapy has been successfully employed in clinical practice in recent years. This study aimed to explore the emerging trend of targeted immunotherapy in MG and summarize the knowledge structure through bibliometric methods. Methods The Web of Science Core Collection database (WoSCC) was chosen to retrieve the literature on targeted immunotherapy for MG. Two bibliometric analysis software, VOSviewer and CiteSpace, and bibliometric online platform were mainly used to evaluate the contributions from countries/regions, institutions, journals, and authors through the construction and visualization of bibliometric networks. By systematically reviewing a knowledge domain, future research developments were determined. The R version 4.1.2 and Microsoft Excel 365 were used for statistical analysis. Results A total of 562 original articles and 262 reviews relevant to MG targeted immunotherapy were included. The number of publications on targeted immunotherapy for MG exhibited a two-phase advancement. The first stage showed a steady growth trend from 1998 to 2016, with an annual number of no more than 35 publications. The second stage revealed an explosive growth trend from 2017, reaching a peak number of publications in 2020. The United States ranked first in the number of publications, citations, and h-index. The author with the highest citation and h-index was Vincent A. And 28.03% of the articles were published in the top 10 journals. In addition to “myasthenia gravis”, the keyword with the highest consideration was “rituximab”, followed by “double-blind”, which indicate research hotspots gradually from basic research to clinical research over time, especially in the field of targeted immunotherapy. The MG treatment has entered a personalized precision treatment phase. Exploration into new target molecules and conducting high-quality randomized controlled trials on existing biological agents are the further research direction. Conclusion The current study summarized the global research trends concerning targeted immunotherapy for MG. Research interests gradually advanced from basic research to clinical research. MG treatment has entered a personalized precision treatment phase. Further investigations into new target molecules and high-quality randomized controlled trials on existing biological agents are required urgently to direct future immunotherapy research.